Preparation and characterization of biopolyol from liquefied oil palm fruit waste: part 2 - Kormin, Shaharuddin; M. Rus, Anika Zafiah (Trans Tech Publications, 2017)
Oil palm fruit waste (OPFW) was conducted using polyhydric alcohol (PA) as liquefaction solvent with H2SO4 in three different OPFW/PA ratio (1/2, 1/3 and 1/4). During the liquefaction, cellulose, semi-cellulose and lignin are decomposed, which results in changes of acid value and hydroxyl value. The liquefied OPFW were characterized by Fourier Transform infrared (FT-IR) spectroscopy. The hydroxyl and acid values of the liquefied oil palm fruit waste (OPFW) varied with the liquefied conditions. It was observed that with an increase in the liquefaction solvent (PA) amount in the mixture resulted in a high acid value and hydroxyl value for the OPFW. FT-IR spectroscopy analysis showed that the resulting biopolyol was suitable monomer for polyurethane (PU) synthesis for the production of PU foams.